Long-term In Vitro Treatment of Human Glioblastoma Cells with Temozolomide Increases Resistance In Vivo through Up-regulation of GLUT Transporter and Aldo-Keto Reductase Enzyme AKR1C Expression - Le Calvé, Benjamin (Neoplasia Press Inc., 2010)
Glioblastoma (GBM) is the most frequent malignant glioma. Treatment of GBM patients is multimodal with maximum surgical resection, followed by concurrent radiation and chemotherapy with the alkylating drug temozolomide (TMZ). The present study aims to identify genes implicated in the acquired resistance of two human GBM cells of astrocytic origin, T98G and U373, to TMZ. Resistance to TMZ was induced by culturing these cells in vitro for months with incremental TMZ concentrations up to 1 mM. Only partial resistance to TMZ has been achieved and was demonstrated in vivo in immunocompromised mice bearing orthotopic U373 and T98G xenografts. Our data show that long-term treatment of human astroglioma cells with TMZ induces increased expression of facilitative glucose transporter/solute carrier GLUT/SLC2A family members, mainly GLUT-3, and of the AKR1C family of proteins. The latter proteins are phase 1 drug-metabolizing enzymes involved in the maintenance of steroid homeostasis, prostaglandin metabolism, and metabolic activation of polycyclic aromatic hydrocarbons. GLUT-3 has been previously suggested to exert roles in GBM neovascularization processes, and TMZ was found to exert antiangiogenic effects in experimental gliomas. AKR1C1 was previously shown to be associated with oncogenic potential, with proproliferative effects similar to AKR1C3 in the latter case. Both AKR1C1 and AKR1C2 proteins are involved in cancer pro-proliferative cell chemoresistance. Selective targeting of GLUT-3 in GBM and/or AKR1C proteins (by means of jasmonates, for example) could thus delay the acquisition of resistance to TMZ of astroglioma cells in the context of prolonged treatment with this drug.